1998
DOI: 10.1074/jbc.273.25.15714
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Plasma Phospholipid Transfer Protein mRNA in Normal and Emphysematous Lungs and Regulation by Hypoxia

Abstract: The lung is the major site expressing plasma phospholipid transfer protein (PLTP) mRNA in humans and mice, suggesting that this protein might have an important role in maintaining normal function of this organ. In the lung of human collagenase transgenic mice, an emphysematous animal model, PLTP mRNA was 3-fold higher than in control mice. However, the mRNA in other tissues was not changed. To further assess the expression and function of PLTP, we measured PLTP mRNA level in lung tissue of two emphysematous pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…In plasma, PLTP transfers phospholipids, but not neutral lipids, between lipoprotein particles ( 13 ). The PLTP gene is also highly expressed in alveolar type II cells and is induced during hypoxia and in emphysema ( 14 ), indicating surface protective properties. Notably human lung tissue, where PLTP is found in an air-water environment (i.e., similar to tear fl uid), displays high PLTP expression levels compared with other tissues.…”
Section: Immunoprecipitation Of Pltp-protein Complex With Monoclonal mentioning
confidence: 98%
See 2 more Smart Citations
“…In plasma, PLTP transfers phospholipids, but not neutral lipids, between lipoprotein particles ( 13 ). The PLTP gene is also highly expressed in alveolar type II cells and is induced during hypoxia and in emphysema ( 14 ), indicating surface protective properties. Notably human lung tissue, where PLTP is found in an air-water environment (i.e., similar to tear fl uid), displays high PLTP expression levels compared with other tissues.…”
Section: Immunoprecipitation Of Pltp-protein Complex With Monoclonal mentioning
confidence: 98%
“…The complex, also containing trace amounts of 14 [C]DPPC, was incubated together with purifi ed PLTP and PLTP distribution was investigated using size exclusion chromatography (SEC). Approximately 80% of the radioactive label was recovered from the BSM-PC complex after cholate dialysis.…”
Section: Characterization Of the Mucin-pltp Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular calcium overload further facilitated the release of pro-inflammatory mediators, which would cause strong contraction and thrombosis of microcirculation. Thus energy metabolism in tissues was disordered and ATP production was reduced [12][13][14][15][16] . In addition, large quantities of free radicals produced during acute pancreatitis would cause phospholipids re-distribution in cell membrane.…”
Section: Activity Of Intracellularmentioning
confidence: 99%
“…19 The human lung tissue, where PLTP is found at an air-water environment (ie, similar to the tear fluid), displays high levels of PLTP compared with other tissues. PLTP is highly expressed in alveolar type II cells, and, notably, is induced during hypoxia and in emphysema, 20 suggesting novel surface protective properties of this molecule. Recently, we elucidated the mechanism of PLTP-facilitated phospholipid transfer 21 and very recently showed that PLTP interacts with human tear fluid mucins.…”
mentioning
confidence: 99%